Pengaruh Penggunaan Metode Repetitive Terhadap Kemampuan Berbahasa Arab Siswa Sekolah Islam Maktab Ibnu Khaldun - Mutiara; Nurman Ginting (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Teaching Arabic to students aged 6-8 years at Maktab Ibnu Khaldun Islamic School presents significant challenges, including disparities in students' language skills and the extended teaching duration required to achieve desired listening and speaking proficiencies. This study aims to evaluate the effectiveness of a repetitive method implemented through an interactive application in enhancing Arabic language skills, particularly in listening and speaking aspects. Utilizing a time series design, 26 students participated in a 4-week learning program using an interactive application that employed the repetitive method. Application usage data and listening comprehension scores were automatically collected during application use, while speaking abilities were assessed through direct observation during face-to-face meetings. Descriptive analysis and multiple linear regression were employed to evaluate the impact of application usage duration and frequency on language abilities, specifically listening and speaking skills. Results demonstrated a significant improvement in both listening and speaking abilities over the 4-week period. The frequency of application usage showed a more significant positive influence than duration, particularly for speaking skills development. This study suggests that integrating repetitive methods through interactive applications can effectively enhance Arabic language learning for young students, potentially transforming Arabic teaching paradigms in Islamic schools and paving the way for more innovative learning methods.